108k views
0 votes
Given the function f(x) = 4(x+3) − 5, solve for the inverse function when x = 3. (1 point)

2 Answers

0 votes

the inverse function is x = 3 is -1

User Yogu
by
5.3k points
5 votes

the function f(x) = 4(x+3) − 5

Lets find the inverse function f^-1(x)

step 1: Replace f(x) with y

y = 4(x+3) − 5

step 2: Replace x with y and y with x

x = 4(y+3) - 5

step 3: Solve for y

x = 4(y+3) - 5

x = 4y +12 -5

x= 4y + 7 (subtract 7 on both sides)

x - 7 = 4y (divide by 4 on both sides)


(x-7)/(4)=y


f^(-1)(x)=(x-7)/(4)

Given : x = 3

We plug in 3 for x in the inverse function


f^(-1)(x)=(3-7)/(4) = -1

the inverse function when x = 3 is -1


User Adam Michalski
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.